THE MAIN REASONS AND FACTORS FOR ORGANIZING SOCIAL PSYCHOLOGICAL SERVICES AMONG THE POPULATION - Gulbahor Bozorova (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2025)
In our rapidly developing era, both the science and practice of social psychology are developing, and the educational process is improving accordingly. The study of social psychology among the population and the organization of services are important activities aimed at understanding the social and psychological relationships between people. This process is aimed at understanding the role of people in society, their needs, feelings and organizing services that are appropriate for them. Social psychology and the organization of services are important in solving the problems of society and making clear and effective decisions.